2019
DOI: 10.1007/s10741-018-09765-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of amlodipine and hydrochlorothiazide therapy and the quest for improved control of hypertension: a mini review

Abstract: Blood pressure (BP) is a complex trait that is regulated by multiple physiological pathways and include but is not limited to extracellular fluid volume homeostasis, cardiac contractility, and vascular tone through renal, neural, or endocrine systems. Uncontrolled hypertension (HTN) has been associated with an increased mortality risk. Therefore, understanding the genetics that underpins and influence BP regulation will have a major impact on public health. Moreover, uncontrolled HTN has been linked to inter-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 108 publications
(223 reference statements)
0
29
0
Order By: Relevance
“…Calcium channel blockers (CCBs) are drugs that bind to and block mainly the L-type calcium channels present on cardiac and vascular smooth muscle cells (SMCs) [ 16 ]. They prevent calcium ions from entering into vascular smooth muscles, which results in muscle relaxation and vasodilation and leads to a decrease in vascular resistance and, consequently, diminished arterial BP [ 17 ].…”
Section: Calcium Channel Blocking Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Calcium channel blockers (CCBs) are drugs that bind to and block mainly the L-type calcium channels present on cardiac and vascular smooth muscle cells (SMCs) [ 16 ]. They prevent calcium ions from entering into vascular smooth muscles, which results in muscle relaxation and vasodilation and leads to a decrease in vascular resistance and, consequently, diminished arterial BP [ 17 ].…”
Section: Calcium Channel Blocking Agentsmentioning
confidence: 99%
“…Numerous studies have indicated that the single-nucleotide polymorphisms (SNPs) in genes encoding different ion channels, including the large-conductance voltage and calcium-sensitive potassium channel β1 ( KCNMB1 ), the voltage-gated calcium channels α1C ( CACNA1C ), α1D ( CACNA1D ) and β2 ( CACNB2 ), and ERG potassium channel ( KCNH2 ), can modify the antihypertensive responses to CCB and the risk of adverse cardiovascular outcomes [ 1 , 19 , 20 , 21 , 22 , 23 ]. Furthermore, variations in the genes coding the family of HECT domain E3 ubiquitin ligases (NEDD4L) and ATP-binding cassette subfamily B member 1 (ABCB1) have been shown to participate in the regulation of blood pressure (BP) in response to anti-hypertensive drugs [ 11 , 16 ]. The result of the INVEST-GENES study demonstrated that the KCNMB1 genotype can influence responses to verapamil SR in White, Hispanic, and Black hypertensive patients with cardiovascular disease (CAD) [ 19 ].…”
Section: Calcium Channel Blocking Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypertension is one of the most common risk factors associated with cardiovascular disease, stroke, and can lead to severe complications [1]. Amlodipine, a dihydropyridine calcium antagonist, has therapeutic effect on hypertension and angina pectoris [2]. Amlodipine is an racemic mixture, including (R) and (S)amlodipine, but only the latter has therapeutic activity [3].…”
Section: Introductionmentioning
confidence: 99%